Návrh a zavedení nápravných opatření ke zvýšení efektivity výroby CP3 - Novák, Marek (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2016)
Cílem této diplomové práce bylo zvýšení efektivity výrobních strojů TORNOS MultiDECO 20/6, které jsou svou konstrukcí v České republice stále ojedinělé. Na základě získaných dat při analýze procesu bylo zjištěno několik oblastí, kde lze docílit zvýšení efektivity strojů. Pro zlepšení bylo uvedeno do praxe několik drobných vylepšení na stroji. Dalším krokem bylo zjištění příčin zvýšené spotřeby nástrojů a návrhu k jejich snížení.

The goal of this master thesis was increase production efficiency of turning machine TORNOS MultiDECO 20/6, which are unique in the Czech Republic by their contruction. Based on data analyzed has been found few areas, where are possible improve operations to increase production efficiency. For improving production efficiency has been implemented several real devices on the turning machine. The next step has been identified the cause of increase consumption of cutting tool and proposal for reduce of used cutting tool.
Proposal and implementation of improvement action to increase production efficiency CP3
Keywords: Efektivita; zvýšení; analýza; TORNOS MultiDECO 20/; Efficiency; increase; analyze; TORNOS MultiDECO 20/6.